Multimodal Neural Probes with Small Form Factor Based on Dual‐Side Fabrication. Issue 2 (30th October 2022) - Kim, Mi Kyung; Leong, Jia Chee; Jo, Yehhyun; Kook, Geon; Lee, Hyunjoo J.
Abstract: Monitoring both individual neuronal spikes and neurotransmitters released from a specific brain region plays a significant role in understanding neuronal circuits and brain functionalities. While polymer neural probe offers distinctive advantages of flexibility, optical transparency, and biocompatibility, achieving high‐density recording with multifunctionalities and multimodality is still a challenge due to limited microfabrication techniques. Here, a multimodal polymer neural probe array based on a dual‐side fabrication process with the potential for high‐density neural recording and electrochemical neurotransmitter detection is presented. The developed dual‐side fabrication allows the placement of a larger number of microelectrodes and multimodal sensors without increasing the probe dimension by utilizing both sides of the shank. Using the dual‐side fabrication, a dual‐sided SU‐8 neural probe array is fabricated which consists of an array of gold and platinum microelectrodes and a micron‐scale three‐electrode system. Moreover, the design space of the micron‐scale three‐electrode systems on the dual‐side neural probe is explored. Through successful in vivo neural spike recording and dopamine (DA) measurements in a brain phantom using the fabricated dual‐side neural probe, it is confirmed that the dual‐sided microfabrication is a reliable and viable solution. Abstract : A multimodal polymer neural probe array based on a dual‐side fabrication process with the potential for high‐density neural recording and electrochemical neurotransmitter detection is presented. The dual‐side fabrication allows the placement of a larger number of microelectrodes and multimodal sensors without increasing the probe dimension by utilizing both sides of the shank.